Austria : Publication of Financial Sector Assessment Program Documentation-Technical Note on Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT). - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This Technical Note sets out the findings and recommendations made in the context of the 2019 Financial Sector Assessment Program for Austria in the areas of Anti-Money Laundering/Combating the Financing of Terrorism. It provides a targeted review of Austria's progress in addressing the Money Laundering/Terrorism Financing vulnerabilities. Several initiatives, the amendments introduced to the Financial Markets Anti-Money Laundering Act, the Beneficial Owners Register Act, and other sectoral laws have led to significant enhancements of the legal and regulatory framework which resulted in a number of upgrades on technical compliance ratings by the Financial Action Task Force in the context of the two follow-up reports. The authorities took steps to transpose the Fourth and the Fifth Anti-Money Laundering Directives into national legislation. Steps have been taken to improve the legal and regulatory framework that applies to lawyers, notaries and tax advisors, and other Designated Non-Financial Business and Professions, but there is room for enhancing implementation. The authorities have recently adopted a comprehensive set of reforms to enhance entity transparency, including through the establishment of a Register of Beneficial Ownership.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet